PROGRAM PEMERINTAH DAERAH KABUPATEN ACEH TENGAH DALAM MENCAPAI SWASEMBADA DAGING SAPI - Hajar Ashwad; R. Hamdani Harahap; Humaizi Humaizi (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2020)
The purpose of this research is to know the implementation of livestock cattle fattening program in ketapang livestock area of Aceh Tengah Regency and to analyze the supporting factors and inhibiting factors in the implementation of livestock cattle fattening program in ketapang cattle region of Central Aceh Regency. The analytical method used descriptive qualitative. Primary data collection is done through interviews distributed to 9 resource persons including livestock service officers, bappeda, extension farms, and breeders located in the area of livestock. From the results of field research shows that the program implemented to achieve self-sufficiency of meat indicated to fail because of financial mismatch budget with the results achieved.